Kandungan Informasi Laba dari Nilai Wajar Aset Keuangan Bank - Ira Geraldina (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This study aims to examine the effect of the fair value of financial assets on information content of bank future earnings after the mandatory adoption of Indonesia Financial Accounting Standards No. 50 55 (or Pernyataan Standar Akuntansi Keuangan 50 55, Revised 2006) on the Financial Instruments: recognition, measurement, and presentation. The financial assets analysed in this study are the fair value measured assets, namely profit or loss, available for sale, held to maturity, and loans and receivables. This study uses 138 publicly listed bank year samples for 2006-2012 periods. Using panel data analysis, the results show that the information content of banks future earnings has increased after the mandatory adoption of PSAK 50 55, but the use of the fair value of financial assets has reduced the information content of banks future earnings. The financial asset that is classified as available for sale may contribute to this reduction of information content of banks future earnings.